Prediction of cardiac conduction disorders using the methods of mathematical analysis - S. Yu. Nikulina; A. A. Chernova; S. S. Tretyakova; D. A. Nikulin (Российский кардиологический журнал)
Aim. To study the possibility of using the genotypes of the TBX5 gene as independent variables for predicting the development of idiopathic disorders of atrioventricular and intraventricular conduction in individuals of the East Siberian population.Material and methods. The study involved 260 patients with idiopathic disorders of atrioventricular and intraventricular conduction and 263 people in the control group. Among patients with idiopathic cardiac conduction disorders (CCD), 71 patients had atrioventricular block (AVB), 84 patients had right His bundle branch block (RBBB) and 105 patients had left His bundle branch block (LBBB). Among patients with idiopathic CCDs 136 were men, 124 — women. The mean age of persons with CCD was 40,72±18,35 years. There were 135 men and 128 women in the control group. The mean age of the control group was 41,34±17,26 years. The patients underwent a clinical and instrumental examination (electrocardiography (ECG), echocardiography, bicycle ergometry, Holter ECG monitoring, coronary angiography, magnetic resonance imaging of the heart, myocardial scintigraphy) and molecular genetic testing of the TBX5 genotypes. Statistical processing of the material was carried out using the Excel 2010, Statistica for Windows 70 and SPSS 20 software.Results. The AA genotype of the TBX5 gene reduces the risk of AVB in the group of women. The presence of AA and AG genotypes is a protective factor in the development of LBBB. The risk of LBBB, obtained by the method of logistic regression, was 34,3%. The resulting model predicts the absence of LBBB with a likelihood of 973%. The development of LBBB was correctly predicted in 9,3% of observations.Conclusion. The genotypes of the TBX5 gene can be used as an independent variable to predict disorders of atrioventricular and intraventricular conduction.